Frequencies New Delhi Metallo-?-Lactamase (NDM) in Klebsiella pneumoniae Isolates from Clinical Samples in Al-Basrah Governorate, Iraq - Mozan, Intithar M.; Al-Amara, Saad S. M. (Scientific Journal of Medical Research, 2023)
Background: Metallo-?-lactamases (MBL) genes are crucial for resistance to antibiotics, and early detection is essential for infection control and prevention of nosocomial outbreaks. Methods: One hundred fifty clinical samples from Basrah hospitals were collected between October and December 2022 and categorized equally into 50 samples for each sputum, urine, and wound swab. K. pneumoniae isolates were identified morphologically and tested on MacConkey and blood agar. The Klebsiella pneumoniae chromogenic medium and Vitek®2 system was used as confirmation tests. Genomic DNA extracted from K. pneumoniae isolates using a commercial purification kit. The DNA extraction was amplified using PCR for 16S rDNA amplification K. pneumoniae isolates using a specific primer of approximately (130bp). K. pneumoniae carbapenemase (KPC) chromogenic agar and modified hodge test, according to CLSI were used to test the K. pneumoniae isolates for detect the ability of carbapenemase production. Plasmid DNA was extracted from K. pneumoniae isolates and plasmid DNA was amplified using PCR to detect the blaNDM gene using a specific primer of approximately (621bp). Results: From November to December 2022, one hindered fifty samples were investigated for bacterial growth, of which gave 82 (56%) were positive and 68 (45.4%) had negative results. Grame-positive bacteria were 28(34.1%), while Gram-negative bacteria were 54(64.9%), including Klebsiella pneumonia 32(59.26%), E. coli 16 (29.63%), Klebsiella spp. 3 (5.56%), Pseudomonas spp. 2 (3.7%), and 1(1.85%) Proteus spp. All K. pneumoniae isolates showed mucoid pink, white, and purple appearances on MacConkey agar, blood agar, and K. pneumoniae chromogenic medium, respectively. The vitek®2 system showed 100% accuracy results in biochemical tests and K. pneumoniae medium. The PCR technology was used to diagnose gene 16S rDNA. The results showed that all (n = 32) K. pneumoniae isolates had a molecular weight of (130 bp) when compared with the standard molecular DNA ladder (200 bp). On the other side, the (n=32) K. pneumoniae isolates tested on Klebsiella pneumoniae carbapenemase chromogenic agar and modified Hodge test, 16 (50%) showed positive results and 16 (50%) showed negative results for carbapenemase production in both methods. On the other side PCR molecular diagnostics the blaNDM gene results showed that all (n = 32) K. pneumoniae isolates revealed a molecular weight of (621 bp), when compared with the standard molecular DNA ladder (200 bp). Conclusions: To select the best treatment and avoid losses time and money, use Klebsiella pneumoniae carbapenemase (KPC) chromogenic agar, modified Hodge test, and PCR techniques for daily antibiotic susceptibility testing in hospital and private clinical laboratories.